A Morphological Analysis On Derivational Affixes (Suffix) -Ion And -Ation Used In Oxford Learner's Pocket Dictionary - Nursanti, Dyah Retno, Drs. Sigit Haryanto, M.Hum, Siti Fatimah, S.Pd, M.Hum (2013)
This research paper aims at clarifying the similarities and differences between the usage of suffix -ion and -ation in Oxford Learner's Pocket Dictionary, describing the characteristics of suffix -ion and -ation in Oxford Learner's Pocket Dictionary. In achieving the objectives, the researcher uses descriptive qualitative as the type of the research. The data source of this research is Oxford Learner's Pocket Dictionary. In collecting the data the writer uses documentation and the steps are reading the dictionary, underlying the word that use suffix -ion and -ation found in dictionary, classifying and writing the data. The technique of analyzing data of this research are identifying the data, classifying and describing the data based on similarities, differences, characteristics, and drawing conclusion. From the result of analysis, it can be drawn some conclusions. Firstly, the similarities between the usage of suffix -ion and -ation is in the function of each suffix and the differences between the usage of suffix -ion and -ation is related to the characteristics of each suffix. Secondly, the characteristics of suffix -ion: The suffix following the noun morpheme with final letter consonant [p]: 1 datum, the suffix following the verb and noun morphemes with final letter consonant [s]: 13 data, the suffix following the noun and adjective morphemes with final letter consonant [x]: 2 data. Then the characteristics of suffix -ation: the suffix following the adjective morpheme with final letter consonant [c]: 4 data, the suffix following the verb morphemes with final letter consonants [l] 3 data, [m] 5 data, [n] 3 data, and [x] 3 data, the suffix following the noun morphemes with final letter consonant [y]: 2 data.